Revealing the percolation–agglomeration transition in polymer nanocomposites via MD-informed continuum RVEs with elastoplastic interphases - Richter, Eva; Possart, Gunnar; Steinmann, Paul; Pfaller, Sebastian; Ries, Maximilian (Composites Part B-Engineering, 2024)
This contribution builds the concluding step of a multiscale approach to effectively capture the mechanical behavior of polymer nanocomposites (PNCs), in this case, silica-modified polystyrene. By introducing continuum-based representative volume elements (RVEs) that employ previously identified elastoplastic property gradients for the interphases surrounding the fillers, the effects of particle size, particle volume fraction, and agglomeration on the mechanical performance are investigated. Uniaxial tension tests are simulated with the respective finite-element RVEs, and stress–strain curves are derived. The elastic and plastic material properties of the RVE can then be extracted and analyzed quantitatively by fitting the stress–strain curves with a Voce-type elastoplasticity formulation. At small degrees of agglomeration, i.e., good particle dispersion, in combination with sufficiently large particle volume fraction, percolation bands form, leading to improved elastic and plastic properties. Higher degrees of agglomeration or particle clusters behave like large single particles, which has an adverse effect, i.e., the nanoscale size effect is thereby neutralized. Therefore, the precise MD-informed elastoplastic interphase representation of our RVEs enables the investigation of the transition from beneficial percolation to unfavorable agglomeration. Ultimately, this contribution establishes a link between the effects of particle size, particle volume fraction, agglomeration, and percolation, which have so far only been discussed separately in the literature. Our methodology offers new insights into the structure–property relations of PNCs and their resulting mechanical behavior. The underlying multiscale approach with a systematic transition from molecular to microscopic scales is required to complement experimental observations and exploit the full potential of PNCs.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Agglomeration; Finite elements; Interphase; Mechanical properties; Modeling and simulation; Nanocomposites; Percolation bands; Polymer composites; Size effect